توصيف الصّرف العربيّ: أبنية الأفعال أنموذجًا - +جميلة غريب, أ.د خليفة صحراوي (Revues faculté des lettres et des langues, 2017)
ملخــــــص:      في ظلّ التطوّر التّكنولوجي؛غدت الحاجة ماسّة لتوصيف اللّغة العربيّة ثم حوسبتها،السّبيل الوحيد للتّقدّم في العديد من التّطبيقات اللّغويّة الحاسوبيّة من قبيل:التّعرّف الآلي على الصّوت،وتحويل النّص المكتوب إلى منطوق،وَتقنيّات التّحليل الصّرفيَ والنّحويّ والدّلالي،وما يؤسّس عليها من برامج تخدم الفهرسة والتّرجمة والتّعليم. وقد تعامل الدّرس اللّساني الحديث مع الصّرف مورد التّوسّع،والانفتاح اللّغويّ بما يوفّره من وسائل عديدة لإنشاء كلمات جديدة لإثراء اللّغة والزّيادة من خصوبتها المعجميّة،لذا فنجاح حوسبة بقيّة المستويات اللّغويّة قائمة عليه.لأجل ذلك اختارت الدّراسة جانبّا منه لتوصيفه وهو(أبنية الأفعال)متّبعة المنهج التّطبيقيّ. Abstract:  “ Descriptiveness of Arabic morphology:  Verbal model structures” Facing the huge technological progress, the need for Arabic language processing and its descriptiveness has become crucial. Indeed, this computerization is the only way to develop linguistic research fields such as voice recognition, conversion text into audio file and the morphological, syntactical and semantic al analysis  technics  and all other applications which are based on this analysis as indexing, machine translation and e-learning. On the other hand, the recent linguistic discourse considers the morphology as a source of a linguistic expansion due to the multitude of tools that provided to create neologisms, enrich the Arabic language and expand their vocabulary. Therefore, the successful processing of all these levels depends closely of the success of the morphological analysis. For this reason, our study addresses the   descriptiveness of one of its components, namely the verbs structuring following an empirical approach.